THE INFLUENCE OF CELEBRITY ENDORSEMENTS AND ELECTRONIC WORD-OF-MOUTH OF GENERATION Z PURCHASE DECISION OF SCARLETT WHITENING PRODUCTS - Kezia T. I Tumundo; Paulus Kindangen; Emilia M Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Technological developments in this era make many things easy, from accessing information to shopping on the internet. These days, many people choose to type what they will buy in internet searches and the results of these searches can have an effect on purchase decision. The higher growth rate of social media users makes entrepreneurs choose marketing strategies by utilizing the internet to communicate, provide information and promote their business to consumers. The purpose of this study is to find out whether the influence of celebrity endorsement and electronic word-of-mouth on Generation Z’s purchase decision of Scarlett Whitening products. This study uses quantitative method and the researchers distributed questionnaires and samples and used 100 respondents. The results of this study found that celebrity endorsement and electronic word-of-mouth partially had a significant positive effect on Generation Z’s purchase decision of Scarlett Whitening products and the results also showed that celebrity endorsement and electronic word-of-mouth simultaneously had a positive and significant effect on generation z’s purchase decision.